Integração financeira, poupança externa e convergência de renda: teoria e evidência - Aderbal Oliveira Damasceno (Brazilian Journal of Political Economy, 2011)
The conventional argument favoring capital controls elimination is based on the predictions from the neoclassical model: free international capital mobility would allow capital flows from country where capital is abundant to countries where capital is scarce and the outcome in a global perspective is efficient allocation of savings and income convergence. Within this perspective, financial integration would be particularly beneficial for developing countries resulting in external savings import, temporary increase in per-capita GDP growth rate and a permanent increase in the per-capita GDP level. Using data for a sample of 105 countries from 1980 to 2004 the evidences show that capitals flows from developing to developed countries and that international financial integration and external savings do not increase the conditional convergence rate.